(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate the protective role of virgin coconut oil and corn oil in phenytoin induced toxicity of rat on the basis of histomorphology of seminiferous tubules. Study Design: Experimental study Place and Duration of Study: This study was conducted at the department of Anatomy of Al-Tibri Medical College and Hospital, for a period of six months from October 2018 to November 2019. Materials and Methods: 48 numbers of male albino rats were randomly selected with weight between 150-250gms. Four different groups were made on the basis of therapeutic agents. Group A control, Group B phenytoin induced intra-peritoneal, Group C virgin coconut oil plus phenytoin and Group D corn oil plus phenytoin. The sample was taken by given anesthesia and both testes were removed through dissection at 4th, 5th and 6th week. The sample was preserved for tissue processing and staining. Tubular dimension were measured through micrometry at 400x, mean of five different tubules from five different field areas were taken and one way ANOVA followed by post hoc tukey’s test was applied to evaluate the significant difference among different groups. P value considered to be significant <0.05 Results: Mean value of tubular dimension was significantly reduced in phenytoin induced toxic group, while in group A and C shows significant restoration of tubular dimension as compared to group D on three different week. Conclusion: Virgin coconut oils showed significant restoration of seminiferous tubules dimension when used along with phenytoin for 6 weeks in comparison of corn oil. Virgin coconut oil showed significant ant oxidative effects and alter the toxic effects of drugs if administered simultaneously